S9.4a Ocular infections by melanized fungi Curvularia lunata and Lasiodiplodia theobromae: Antifungal susceptibility and clinical outcome. (20th September 2022) - Mitra, Sanchita; Garg, Prashant; Murthy, Somasheila; Dave, Vivek Pravin
Abstract: S9.4 Free oral presentations (late breaking), September 23, 2022, 4:45 PM - 6:15 PM: Purpose: To report antifungal susceptibility and clinical correlations in melanized fungal isolates of Curvularia lunata and Lasiodiplodia theobromae from ocular infections. Methods: Antifungal susceptibility testing was performed by broth microdilution testing, following Clinical and Laboratory Standard Institute guidelines, of 17 C. lunata and 13 L. theobromae isolates from monomicrobial infections of microbial keratitis or fungal endophthalmitis patients. Isolates resistant to ≥2 classes of antifungals were considered as multidrug-resistant (MDR). The panel of antifungals tested were amphotericin B, natamycin, voriconazole, ketoconazole, fluconazole, itraconazole, posaconazole, and caspofungin. Results: Voriconazole showed the highest susceptibility (83.3% isolates) followed by natamycin (80%), fluconazole (80%), itraconazole (76.7%), ketoconazole (70%), posaconazole, and caspofungin (66.7% each) and lastly amphotericin B (63.3%). For treatment, all patients received topical natamycin, and few received additional oral ketoconazole or intraocular voriconazole. MDR isolates led to the poorer clinical outcomes ( P =.015) in patients. But natamycin resistance alone did not show unfavorable outcomes ( P =.28), though this was the most frequent drug used topically in fungal ocular infections. Conclusion: Melanized fungi causing ocular infections have varying susceptibility to different antifungal agents. Most effective drug as seen in vitro in our study, was voriconazole. Significant resistance to amphotericin B, which is the most common antifungal used in intravitreal injections, was noted. MDR isolates overall, had poorer clinical outcomes.